FORMULATION OPTIMIZATION AND EVALUATION OF MOUTH-DISSOLVING TABLETS OF FENOPROFEN CALCIUM DIHYDRATE BY SUBLIMATION PROCESS - NARWARIYA, SHAILENDRA SINGH; JAIN, SUMAN; MUTHUMANICKAM, ALAGUSUNDARAM (International Journal of Applied Pharmaceutics, 2025)
Objective: An anti-inflammatory analgesic called Fenoprofen Calcium Dihydrate (FCD) is used to treat mild to moderate pain as well as the symptoms of osteoarthritis and rheumatoid arthritis. The goal of the current study was to formulate, optimize, and assess FCD Mouth Dissolving Tablets (MDT). Methods: The sublimation process was used to create the MDT of FCD using a variety of superdisintegrants, including as Indian-414, Croscarmellose Sodium (CCS), and Sodium Starch Glycolate (SSG). Skimmed milk powder serves as an excipient, solubility enhancer, and taste-masking ingredient. One subliming substance used in the sublimation process is camphor. The design can be generated with three center points per block with 15 runs. The formulas were optimized using the Box-Bhenken Design (BBD) with three independent variables (X1, X2, X3) at three levels (-1, 0,+1) with a minimum to maximum range. R1, R2, and R3, whose titles were wetting time, drug content, and disintegration time, respectively, were the response or dependent variables. Results: Fifteen MDTs of FCD formulations with independent and dependent variables are optimized using BBD. The smooth flow is demonstrated by the micrometric study. All compositions, including powder blends, have flow abilities that vary from good to exceptional, with values between 25.11 and 32.87. The hardness of the tablet ranged from 2.3±0.19 to 2.9±0.13 kg/cm2. The findings indicated that the wetting duration was between 32±1.38 and 39±1.72 sec, and the water absorption ratio ranged from 65±1.58 to 83±1.8%. All produced formulations had drug contents ranging from 94.5±0.74 to 99.69±0.59. The range of the disintegration time was 39±2.38 to 47±1.46 sec. The proportion of FCD from the formulations S3, S8, and S13 was 99.57, 99.64, and 99.98 after 90 min. At the p0.05 level, the formulations S3, S8, and S13 demonstrated good stability and statistical significance. Conclusion: Sublimation was used to successfully construct FCD MDTs using a range of superdisintegrants, and the outcomes were good in every way.